Pencegahan Covid-19 Melalui Edukasi PHBS Pada Masyarakat Dusun Moncongloe Bulu, Kabupaten Maros - Sainah, Sainah Iin; Sumaryanti, Sumaryanti; Sofyan, Sofyan (Patria Artha Journal of Community (PKM), 2021)
The aim of this community service is to immediately educate people on the importance of living  a  clean  and  healthy  lifestyle  (PHBS)  to  protect Covid-19.  To  prevent  Covid-19,  the method   used   is   theory-based   education   and   practice   PHBS   with   three   stages,   namely preparation,  implementation,  and  evaluation. Residents  of  Saliong  Village,  Moncongloe Bulu RT 15  District, Buru  Regency  are  the  recipients  of  this  community  service  activity.  As  a  result  of  this  community service activity, residents of Moncongloe Bulu Village gain knowledge through the theory and practice -based  education  stages  on  how  to  be  aware of  and  deal  with  Covid-19,  how  to  apply PHBS  and  types  of  high  protein  foods  and  drinks,  how  to  use  masks  (differentiate  between disposable  and  reusable  masks),  and  how  to  wash  your  hands  properly.  Residents  of  Moncongloe Bulu Village  will  be  able  to  live  a  clean and  healthy  lifestyle  as  a  result  of  this  education,  such  as knowing  how  to  wash  their  hands  correctly  and  adequately,  how  to  use  masks  (knowing  the types  of  disposable  masks  and  types  of  re-washing  masks),  avoiding  direct  contact  with  other residents,  and complying  with  health  protocols,  establishing  a  pattern  and behavior  of healthy living  in  the  community  through  the  consumption  of  healthy  nutritious  food,  regular  exercise, and routine health checks at the nearest Health Service Center.Keywords: PHBS, Covid-19, Health Promotion